Sirt5 Deficiency Causes Posttranslational Protein Malonylation and Dysregulated Cellular Metabolism in Chondrocytes Under Obesity Conditions. (December 2021) - Zhu, Shouan; Batushansky, Albert; Jopkiewicz, Anita; Makosa, Dawid; Humphries, Kenneth M.; Van Remmen, Holly; Griffin, Timothy M.
Objective: Obesity accelerates the development of osteoarthritis (OA) during aging and is associated with altered chondrocyte cellular metabolism. Protein lysine malonylation (MaK) is a posttranslational modification (PTM) that has been shown to play an important role during aging and obesity. The objective of this study was to investigate the role of sirtuin 5 (Sirt5) in regulating MaK and cellular metabolism in chondrocytes under obesity-related conditions. Methods: MaK and SIRT5 were immunostained in knee articular cartilage of obese db/db mice and different aged C57BL6 mice with or without destabilization of the medial meniscus surgery to induce OA. Primary chondrocytes were isolated from 7-day-old WT and Sirt5 −/− mice and treated with varying concentrations of glucose and insulin to mimic obesity. Sirt5-dependent effects on MaK and metabolism were evaluated by western blot, Seahorse Respirometry, and gas/chromatography-mass/spectrometry (GC-MS) metabolic profiling. Results: MaK was significantly increased in cartilage of db/db mice and in chondrocytes treated with high concentrations of glucose and insulin (Glu hi Ins hi ). Sirt5 was increased in an age-dependent manner following joint injury, and Sirt5 deficient primary chondrocytes had increased MaK, decreased glycolysis rate, and reduced basal mitochondrial respiration. GC-MS identified 41 metabolites. Sirt5 deficiency altered 13 distinct metabolites under basal conditions and 18 metabolites under Glu hi Ins hi treatment. Pathway analysis identified a wide range of Sirt5-dependent altered metabolic pathways that include amino acid metabolism, TCA cycle, and glycolysis. Conclusion: This study provides the first evidence that Sirt5 broadly regulates chondrocyte metabolism. We observed changes in SIRT5 and MaK levels in cartilage with obesity and joint injury, suggesting that the Sirt5-MaK pathway may contribute to altered chondrocyte metabolism that occurs during OA development.